LEGALITY OF ELECTRONIC MEDICAL RECORDS (ELECTRONIC MEDICAL RECORDS) IN THE READINESS OF THE HOSPITAL MANAGEMENT INFORMATION SYSTEM BASED ON THE REGULATION OF THE MINISTER OF HEALTH NUMBER 24 OF 2022 CONCERNING MEDICAL RECORDS - Indra Saputra; Sumarno; Siti Nurhayati (Journal of International Islamic Law, Human Right and Public Policy, 2024)
The problems that arise are related to the legality of medical records, where many hospitals still do not have electronic medical records (EMR) and this is not in line with PERMENKES number 24 of 2022 concerning electronic medical records. This study aims to determine the importance of the Electronic Medical Record (EMR) system in use in the world of health, to find out how ready hospitals are to implement EMR (Based on Regulation of the Minister of Health No. 24 of 2022), to find out how the Legality of Electronic Medical Records (EMR) in the Readiness of the Hospital Management Information System Based on Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records. This study uses an empirical legal research type by looking at the problems of Electronic Medical Records in hospitals and using a statute approach (statutory regulations) by looking at the aspects of PERMENKES. The research results The legal basis used by RSUD for the implementation of EMR are: Law number 17 of 2023 concerning Medical Practice, Law number 44 of 2009 concerning Hospitals. Regulation of the Minister of Health of the Republic of Indonesia Number 1045 / MENKES / PER / XI / 2006 concerning Guidelines for Hospital Services within the Ministry of Health, Decree of the Minister of Health of the Republic of Indonesia Number 129 / MENKES / SK / II / 2008 concerning Minimum Hospital Service Standards. The legality of electronic medical records (EMR) in the readiness of the hospital management information system based on the Regulation of the Minister of Health No. 24 of 2022 concerning Medical Records is the right choice in today's era, and its existence is protected by law. The implementation of medical records at RSUD. dr. A. Tjokro Dipo Lampung Province is good based on the results of purposive sampling. Informants were taken based on certain criteria.